Protective effectiveness of previous SARS-CoV-2 infection and hybrid immunity against the omicron variant and severe disease: a systematic review and meta-regression - Bobrovitz, Niklas; Ware, Harriet; Ma, Xiaomeng; Li, Zihan; Hosseini, Reza; Cao, Christian; Selemon, Anabel; Whelan, Mairead; Premji, Zahra; Issa, Hanane; Cheng, Brianna; Abu Raddad, Laith J; et al. (The lancet. Infectious diseases, 2023)
The global surge in the omicron (B.1.1.529) variant has resulted in many individuals with hybrid immunity (immunity developed through a combination of SARS-CoV-2 infection and vaccination). We aimed to systematically review the magnitude and duration of the protective effectiveness of previous SARS-CoV-2 infection and hybrid immunity against infection and severe disease caused by the omicron variant.